Microstructural characteristics and mechanical properties of carbon nanotube reinforced aluminum alloy composites produced by ball milling - Raviathul Basariya M.; Srivastava V.C.; Mukhopadhyay N.K. (My University, 2025)
The influence of milling time on the structure, morphology and thermal stability of multi-walled carbon nanotubes (MWCNTs) reinforced EN AW6082 aluminum alloy powders has been studied. After structural and microstructural characterization of the mechanically milled powders micro- and nano-hardness of the composite powder particles were evaluated. The morphological and X-ray diffraction studies on the milled powders revealed that the carbon nanotubes (CNTs) were uniformly distributed and embedded within the aluminum matrix. No reaction products were detected even after long milling up to 50. h. Nanotubes became shorter in length as they fractured under the impact and shearing action during the milling process. A high hardness of about 436. ±. 52. HV is achieved for the milled powders, due to the addition of MWCNTs, after milling for 50. h. The increased elastic modulus and nanohardness can be attributed to the finer grain size evolved during high energy ball milling and to the uniform distribution of hard CNTs in the Al-alloy matrix. The hardness values of the composite as well as the matrix alloy compares well with that predicted by the Hall-Petch relationship. © 2014 Elsevier Ltd.